Psychobiotics: potential alternatives to conventional anxiolytics? (Research, Society and Development, 2021)
Understanding that in the last decades psychobiotics, a new class of probiotics, have directed many researchers to focus on studying them in relation to their therapeutic potential for psychic disorders, the present study compiled data from the scientific literature regarding recent discoveries related to psychobiotics as a potential alternative for the treatment of anxiety. For this purpose, an integrative literature review was carried out, through consultations to articles published in the last six years through the PubMed/MEDLINE and SciELO databases, using the following descriptors: "Probiotics and anxiety","Psycobiotcs and anxiety", published in full in English. A total of 267 studies were found, of which merely 14 articles were eligible. At first, the benefits generated by psychobiotics for mental health were discussed, as well as their importance in understanding of the mechanisms involved in the brain-microbiome- intestine axis relationship for psychological disorders, especially anxiety. Through the analysis of selected pre-clinical and clinical studies, it was possible to identify strains of probiotics that have greater potential for psychobiotic candidates, with an emphasis on the treatment of anxiety. In general, studies have shown the effectiveness of psychobiotics, which were able to mitigate the symptoms caused by anxiety disorders, improving central nervous system functions, with low occurrence or absence of adverse effects. Thus, in the future, they can compose a new therapeutic approach for the treatment of anxiety symptoms and other psychiatric comorbidities.